Isoenzyme analysis and relationships among three species in Malaysian Trichoderma isolates. - Shafiquzzaman, Siddiquee; Tan, Soon Guan; Yusuf, Umi Kalsom (Korean Society for Microbiology and Biotechnology (KMB), 2010)
Isozyme and protein electrophoresis data from mycelial extracts of 27 isolates of Trichoderma harzianum, 10 isolates of T. aureoviride, and 10 isolates of T. longibrachiatum from Southern Peninsular Malaysia were investigated. The eight enzyme and a single protein pattern systems were analyzed. Three isozyme and total protein patterns were shown to be useful for the detection of three Trichoderm a species. The isozyme and protein data were analyzed using the Nei and Li Dice similarity coefficient for pairwise comparison between individual isolates, species isolate group, and for generating a distance matrix. The UPGMA cluster analysis showed a higher degree of relationship between T. harzianum and T. aureoviride than to T. longibrachiatum. These results suggested that the T. harzianum isolates had high levels of genetic variation compared with the other isolates of Trichoderma species.